In vitro evaluation of the biocompatibility and bioactivity of a SLM-fabricated NiTi alloy with superior tensile property - Yu Sun; Zhihui Zhang; Qingping Liu; Luquan Ren; Jincheng Wang (Journal of Materials Science: Materials in Medicine)
Abstract Because nickel-titanium (NiTi) alloys have unique functions, such as superelasticity, shape memory, and hysteresis similar to bone in the loading-unloading cycles of their recoverable deformations. They likely offer good bone integration, a low loosening rate, individual customization, and ease of insertion. Due to the poor processability of NITI, traditional methods cannot manufacture NiTi products with complex shapes. Orthopedic NiTi implants need to show an adequate fracture elongation of at least 8%. Additive manufacturing can be used to prepare NiTi implants with complex structures and tunable porosity. However, as previously reported, additively manufactured NiTi alloys could only exhibit a maximum tensile fracture strain of 7%. In new reports, a selective laser melting (SLM)–NiTi alloy has shown greater tensile strain (15.6%). Nevertheless, due to the unique microstructure of additive manufacturing NiTi that differs from traditional NITI, the biocompatibility of SLM-NITI manufactured by this new process requires further evaluation In this study, the effects of the improved NiTi alloy on bone marrow mesenchymal stem cell (BMSC) proliferation, adhesion, and cell viability were investigated via in vitro studies. A commercial Ti-6Al-4V alloy was studied side-by-side for comparison. Like the Ti-6Al-4V alloy, the SLM-NiTi alloy exhibited low cytotoxicity toward BMSCs and similar effect on cell adhesion or cell viability. This study demonstrates that the new SLM-NiTi alloy, which has exhibited improved mechanical properties, also displays excellent biocompatibility. Therefore, this alloy may be a superior implant material in biomedical implantation. Graphical Abstract